Surface Plasmon-Driven Water Reduction: Gold Nanoparticle Size Matters - Qian, Kun; Sweeny, Brendan C; Johnston-Peck, Aaron C; Niu, Wenxin; Graham, Jeremy O; DuChene, Joseph S; Qiu, Jingjing; Wang, Yi-Chung; Engelhard, Mark H; Su, Dong; Stach, Eric A; Wei, Wei David (Journal of the American Chemical Society, 2014)
Water reduction under two different visible-light ranges (λ > 400 nm and λ > 435 nm) was investigated in gold-loaded titanium dioxide (Au-TiO2) heterostructures with different sizes of Au nanoparticles (NPs). Our study clearly demonstrates the essential role played by Au NP size in plasmon-driven H2O reduction and reveals two distinct mechanisms to clarify visible-light photocatalytic activity under different excitation conditions. The size of the Au NP governs the efficiency of plasmon-mediated electron transfer and plays a critical role in determining the reduction potentials of the electrons transferred to the TiO2 conduction band. Our discovery provides a facile method of manipulating photocatalytic activity simply by varying the Au NP size and is expected to greatly facilitate the design of suitable plasmonic photocatalysts for solar-to-fuel energy conversion.